EFFECT OF FOLIAR SPRAYOF GIBBERELLINS, KELATEX (Ca), AND AMINOPLASMAL ON VEGETATIVE GRWOTH AND LEAF NUTRIENT OF POMEGRANATE TREES (Punica granatum L.) CV. MAHDAWI - ALI, DAWOD MOHAMMED; MAYI, AZAD AHMAD (Journal of Duhok University, 2023)
This study was conducted during growing season of 2022 in a private orchard of pomegranate (Punica granatum L.) cv. Mahdawi which is located at Dulib village, Duhok Governorate, Kurdistan region to evaluate the efficacy of foliar spray of, Gibberellins (GA3) Kelatex (Ca) and Aminoplasmal (A). The experiment designed as a factorial experiment in a randomized complete block (RCBD) with three replications, for each treatment and each replicate was represented by one tree. There were three concentrations of Gibberellins (0,50 and 100mg. L-1); three concentration of Ca (0, 200, and 400mg. L-1) and three concentrations of Aminoplasmal (0, 100 and 200ml.L-1) in the study. The results showed that GA3 at 100mg. L-1 had a significant effect on leaf area, leaf dry weight, leaf chlorophyll content, leaf nitrogen content and leaf calcium content when compared to control. On the other hand, that Ca at 400 mg. l-1 had significant effect on leaf dry weight, leaf chlorophyll and leaf calcium content when compared to control, in addition to Aminoplasmal at 200 mg. L-1   had significantly affected leaf area, leaf dry weight, chlorophyll content, nitrogen content, and calcium content. Furthermore, the interaction between (GA3, Ca and A) had significant effect on leaf chlorophyll, leaf calcium content, leaf nitrogen content, and leaf area at concentrations of (100, 400, and 200 mg. L-1) respectively. However, the leaf dry weight was significantly affected at concentrations of (100,200 and 200 mg. L-1) respectively